Rancang Bangun Mesin Pengaduk Adonan Kapasitas 50 kg untuk Efisiensi Produksi Keripik pada UMKM Kripik Wulan 008 di Desa Panimbang Jaya - Lukman David; Muhamad Ja’far Sodik; Gagah Dwiki Putra Aryono; Andika Purnama; Abdul Kohar; Rizqi Ardiansyah (Jurnal Pengabdian Masyarakat Waradin, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, particularly in the food sector, which focuses on snack products such as chips. However, many MSMEs still face production challenges, especially in the dough mixing process that is commonly carried out manually. This condition results in low efficiency, limited production capacity, and inconsistent dough quality. This study was conducted at Kripik Wulan 008 MSME in Panimbang Jaya Village with the aim of designing and implementing a 50-kg capacity horizontal dough mixer as an appropriate technology solution. The mixer was designed using a 2 HP single-phase electric motor with a 1:30 gearbox ratio and a food-grade stainless steel mixing chamber. Testing results showed that the machine could mix 50 kg of dough in 15–20 minutes, which is significantly faster than the manual method requiring more than 40 minutes. After implementation, daily production capacity increased from 50–75 kg to 75–100 kg, with dough quality becoming more homogeneous and hygienic. In addition, operational training provided workers with improved skills in operating and maintaining the machine. Therefore, the application of this horizontal dough mixer has proven effective in enhancing productivity, efficiency, and the competitiveness of food-sector MSMEs in an increasingly competitive market.